Robot-Assisted Unicompartmental Knee Arthroplasty: Increasing Surgical Accuracy? A Cadaveric Study - Iñiguez, Magaly; Negrín, Roberto; Duboy, Jaime; Reyes, Nicolás O.; Díaz, Rodrigo (The Journal of Knee Surgery, 2019)
Unicompartmental knee arthroplasty (UKA) represents 10% of knee arthroplasties. Advantages are better functional results, quicker recovery, shorter hospitalization time, and lower blood loss, among others. However, revision rates are larger than total knee arthroplasty. Among the most important factors that explain this are the implant position and alignment, and the correct surgical indication. Greater accuracy in the implant placement may improve clinical results and increase the rate of implant survival. The objective of this study is to evaluate the precision of the Navio robot-assisted system in the position and alignment of medial UKA compared with the conventional technique. This is an experimental pilot study. Twenty-six cadaveric models were randomized into 2 groups: Robot-Assisted surgery (R) and Conventional Surgery (C). Radiological study was performed pre- and post-surgery, evaluating the medial distal femoral angle (MDFA), medial proximal tibial angle (MPTA), tibial slope, tibiofemoral angle (TFA), sagittal femoral angle (SFA), and size of the femoral and tibial components. The main result measurement was the change in postoperative angulation. The results of this study are MDFA median of 1.07° (0.19–4.5) for group R and 0.12° (0.03–10.4) with a significant difference in variances; a Welch t-test of p = 0.013; and an MPTA of 1.28° (0.05–5.87) for R and 1.3°(0.08–14.1) for C with significantly different variances (p = 0.0064). Size of the femoral component has a difference of p < 0.05 between groups. No differences for dispersion of TFA nor for the size of the tibial component were observed. In conclusion, using robot-assisted UKA allows for greater accuracy in the positioning of the implants and in the prediction of the size of the femoral component.
Keywords: unicompartmental knee arthroplasty; robotics